Rede de poli(dimetilsiloxano) funcionalizado com o grupo amino sobre partículas de carvão ativado para adsorção de íons metálicos - Alves, Galvani Pereira (2017)
Crosslinked 3-aminopropyltrimethoxysilane poly(dimethyl)siloxane was coated on activaed charcoal and hydrophobic characteristics, is functionalized with the crosslinking reagent 3-(aminopropyl) triethoxysilane, obtaining a material with hydrophilic characteristics and the capacity to adsorb metal ions from aqueous media. The elastomeric functionalized network will be spread over the activated carbon particles, with the objective to mimic the porous, increasing the contact surface and adsorptive capacity, making more active sites available for the adsorption. It was synthesized four materials, in which the variable was the reaction mixture time. Stablished the best reaction time, new materials were prepared by varying the mass of activated carbon. The characterization by thermogravimetry (TGA) and infrared spectroscopy with Fourier transformed infrared spectroscopy - attenuated total reflectance (FT-IR) confirmed the formation of the polymeric network proposed and the data obtained by Scanning electron microscopy (SEM) and UV-visible optical spectroscopy (UV-Vis) indicate that the network covered the activated carbon particles. pH and contact time studies were carried out, as well as modeling of the adsorption process using theoretical models of Langmuir, Freundlich, SIPS and Redlich-Peterson from the concentration isotherms in relation to the adsorption process, where it was possible to define the more efficient adsorbent material, called CPND1.